(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
Wireless Sensor Networks (WSNs) are the networks consisting of wireless sensors which transmit and receive information among each other. Such networks are useful in various fields like civil and military applications for security systems, fault detections, etc. Energy optimization is one of the major issues of WSNs to extend the lifetime of these networks. A number of clustering based algorithms like LEACH and SEP are already well known and are used to increase stability of the network. In this paper an effort has been done to propose a protocol, OCEA-LEACH, which is an improvement over LEACH in heterogeneous environment in which the randomized selection of clusters is tried to be centralized and to avoid the redundancy cluster heads tried to be kept well separated with in the region. So, unlike LEACH, cluster heads are chosen based on their available energies which results in better distribution of cluster heads within the region. Simulations results on MATLAB shows that OCEA-LEACH depicts better results than the existing protocols like LEACH and SEP.